Transactions on data hiding and multimedia security VI - Shi, Yun Q.; Emmanuel, Sabu.; Kankanhalli, Mohan S.; Chang, Shih-Fu.; Radhakrishnan, Regunathan; Ma, Fulong; Zhao, Li.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication, and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval, and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. This issue consists mainly of a special section on content protection and forensics including four papers. The additional paper deals with histogram-based image hashing for searching content-preserving copies.
Markovian Rake Transform for Digital Image Tampering Detection -- Embedding Binary Watermarks In Dual-Tree Complex Wavelets Domain for Access Control of Digital Images -- Robust Watermarking of Compressed JPEG Images in Encrypted Domain -- A Progressive Quality Hiding Strategy Based on Equivalence Partitions of Hiding Units -- Histogram-Based Image Hashing for Searching Content-Preserving Copies.
Electronic reproduction.
Keywords: Electronic books; Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Optical pattern recognition